PENGARUH TINGKAT SUKU BUNGA BANK DAN BAGI HASIL TERHADAP DEPOSITO MUDHARABAH - Azzahra, Fathimah Hanoum (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
Baitul Mal wat Tamwil is an incorporated saving and loan cooperation financial institution. Recently, this institution becomes popular in Indonesia along with the muslims spirit to find alternative economic model post monetary crisis in 1997. The BMT is based on the basic principles of economic order in Islamic religion: transparency, mutual willing, trust, and responsibility and particularly its âprofit sharingâ system.Quantitative method is used in this research. The data is secondary data and time series which have been obtained from Mudharabah deposit report and financial statistics of Bank Indonesia. The samples are 24 items from January 2012 to December 2013. The regression analysis is used for partial significant examination between bank interest rate and profit sharing rate and Mudharabah deposit.The result of this research gives explanation that bank interest rate has negative influence to the BMT Amanah Madinah Ngeni Waru Sidoarjo volume of Mudharabah deposit because when the interest rate of commercial or conventional banks increases, the BMT Amanah Madinah Mudharabah deposit increases as well.Then, the profit sharing has negative relation and has no influence to the volume of BMT Amanah Madinah Ngeni Waru Sidoarjo Mudharabah deposit.Keywords: Bank Interest Rate, Profit Sharing Rate, Mudharabah Deposit